The Influence of Internal Audit and Internal Control on Fuel Oil (BBM) Sales Performance(Study at the gas station company PT. Bumi Bagus) - Lana, Kukuh Wira Satra; Bambang, Bambang (PT FORMOSA CENDEKIA GLOBAL, 2024)
Companies need a system to find a problem. A system that is useful and needs to be paid attention to is the existence of an internal audit in PT gas station operations. Bumi Bagus is followed by internal control as a supervisor to achieve its goals. This research aims to find out the effect of internal audits and control on fuel sales performance. The method used in this research is quantitative descriptive. The data used in this research is primary data obtained directly from gas stations PT. Good Earth. The sample used was all petrol station employees of PT. Bumi Bagus, so the total is 30 respondents. The data analysis tool used is SPSS (Statistical Product and Service Solution) version 2.6.